2021
DOI: 10.1186/s12962-021-00313-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis for SilAtro-5-90 adjuvant treatment in the management of recurrent tonsillitis, compared with usual care only

Abstract: Purpose Antibiotics are one possible treatment for patients with recurrent acute throat infections (ATI), but effectiveness can be modest. In view of worries over antibiotic resistance, treatment pathways that reduce recurrence of ATI are essential from a public health perspective. Integrative treatment strategies can be an option but there is still a high demand to provide evidence of their cost effectiveness. Methods We constructed a 4-state Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Two of those studies evaluated tonsillectomy as a prevention strategy for frequently recurring pharyngitis 58 , 59 , and they both found that tonsillectomy was cost-effective compared to usual care. One study found that homeopathic remedy (SilAtro-5–90) as an adjuvant to normal treatment was cost-effective in preventing recurrent pharyngitis 60 . Lastly, a study evaluating strategies to prevent recurrent cellulitis found that antibiotic prophylaxis was not associated with a significant increase in costs but reduced the risk of recurrence by nearly a third 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Two of those studies evaluated tonsillectomy as a prevention strategy for frequently recurring pharyngitis 58 , 59 , and they both found that tonsillectomy was cost-effective compared to usual care. One study found that homeopathic remedy (SilAtro-5–90) as an adjuvant to normal treatment was cost-effective in preventing recurrent pharyngitis 60 . Lastly, a study evaluating strategies to prevent recurrent cellulitis found that antibiotic prophylaxis was not associated with a significant increase in costs but reduced the risk of recurrence by nearly a third 61 .…”
Section: Resultsmentioning
confidence: 99%
“…25 In a subsequent study, adjuvant SilAtro-5–90 was found to be cost-effective in the management of recurrent tonsillitis, compared with usual care only. 26…”
Section: Discussionmentioning
confidence: 99%
“…25 In a subsequent study, adjuvant SilAtro-5-90 was found to be cost-effective in the management of recurrent tonsillitis, compared with usual care only. 26 Another important finding of the trial was deterioration of halitosis (F 2, 28 ¼ 4.311, p ¼ 0.023) and nocturnal breathing (F 2, 28 ¼ 1.249, p ¼ 0.302) subscales of the TAHSI instrument in the AN group, whereas the IHMs revealed significant improvement in these two subscales (halitosis: F 2, 28 ¼ 11.860, p < 0.001; nocturnal breathing: F 2, 28 ¼ 6.190, p ¼ 0.006). However, TAHSI being the secondary outcome measure, drawing inference was not based on these findings.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%